2022
DOI: 10.1016/j.ijhm.2022.103174
|View full text |Cite
|
Sign up to set email alerts
|

The perils of hotel technology: The robot usage resistance model

Abstract: The COVID-19 outbreak has accelerated the development of service robots. However, service robots in some hotels have been put aside despite successful adoption. This study thus focuses on hotel employees' inhibited continuous usage intention by examining the challenges of benefiting from service robots. A robot usage resistance model (RURM) has been proposed based on the results. In this model, lack of authentic anthropomorphous features and low usability as technological characteristics could influence employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 53 publications
5
47
0
Order By: Relevance
“…Further, Ali et al (2022) studied the motivational factors and barriers affecting Generation Z employees’ acceptance to work with service robots in hotels, highlighting the unique characteristics of Generation Z in affecting their technology usage as the future workforce. Some scholars have also started to look at the negative aspects of service robot adoption in hotel industry (Fu et al , 2022) and suggest ways to mitigate such negative impact. For instance, Yu et al (2022) suggested that employee skills such as tech-savviness and social skills could effectively lower their turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Ali et al (2022) studied the motivational factors and barriers affecting Generation Z employees’ acceptance to work with service robots in hotels, highlighting the unique characteristics of Generation Z in affecting their technology usage as the future workforce. Some scholars have also started to look at the negative aspects of service robot adoption in hotel industry (Fu et al , 2022) and suggest ways to mitigate such negative impact. For instance, Yu et al (2022) suggested that employee skills such as tech-savviness and social skills could effectively lower their turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of smart restaurant and dining renders as a new phenomenon of interest in foodservice (Peek, 2021). Given the objective stated above, the present research builds the necessary foundation based on three hospitality research areas: service quality (Lin et al , 2020; Wong and Yang, 2020), AI and robots (Doborjeh et al , 2022; Jiang and Wen, 2020; Pillai and Sivathanu, 2020; Fu et al , 2022) and information technology applications in restaurants and other related contexts (Stylos et al , 2021; Law et al , 2022; Mariani and Baggio, 2022). In particular, we seek to synthesize these streams of work to better assess how technologies, especially AI and robots, are infused within the smart restaurants through the lens of service quality.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In recent years, AI has been applied to various fields, including management for event lodging, travel agencies, supply chains, restaurants and sales and marketing (Davari et al , 2022; Doborjeh et al , 2022; Fu et al , 2022). AI applications in front-line services may focus on assisting or complementing employees doing more routine tasks.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hospitality 5.0 refers “to the extension of the modularity, real-time capabilities, virtualization, decentralization and interoperability design principles of Industry 5.0 to the hospitality industry” ( Pillai et al, 2021 ) is swiftly becoming a mainstream concept in the industry. Specifically, contactless automation technology, mobile technology, robotics, artificially intelligent machines, and virtual and augmented reality are gradually but steadily diffusing into the critical guest touchpoints in the guest consumption journey ( Luo et al, 2021 , Fu et al, 2022 ). This gradual proliferation of service robots is projected to continue.…”
Section: Introductionmentioning
confidence: 99%